Скарб XVII ст. з Некрасового - Коваленко, Ю.О. (Сіверщина в історії України, 2021)
У статті вперше вводиться до наукового обігу скарб речей
XVII ст., виявлений при нез’ясованих обставинах неподалік села Некрасове Глухівського району Сумської області. The article introduces into scientific circulation for the first time the treasure
of things of the XVII century, discovered under unknown circumstances near the
village of Nekrasovo, Hlukhiv district, Sumy region.
A peculiar treasure of late medieval ornaments was accidentally found by one
of the locals near the village of Nekrasove, Hlukhiv district, Sumy region. The find
happened on the southern outskirts of the village.
Probably, things are related to the late medieval settlement, which occupied a
small area on the right bank of the river Esman.
The treasure consisted of 26 Russian and 10 Polish silver coins of the first half
of the 17th century, a copper alloy cross and a silver knife handle. All the finds,
except for the tip of the knife handle, are part of a woman’s jewelry that was once
lost or hidden.
Traditionally, the origin of treasures is associated with some force majeure
circumstances: fires, natural disasters, hostilities, etc. It is possible that the above
items were hidden during the military events that took place in the North in the
first half of the XVII century.
Archaeological, staurographic and numismatic materials originating from the
area where the treasure was discovered are included in the time frame from the
second half of the XVI century. to the beginning of the XVII century. The dating
of jewelry coins from the treasure is limited to the late 20s of the XVII century. In
our opinion, the time when the treasure was hidden was the first half of the 17th
century, but not later than the middle of the 1930s.